The Importance of Total Quality Management and Leadership Communication to Enhance Islamic Quality at Malaysian Civil Service - Adnan, Hassan; Raja Rahman, Raja Roslan; Husain, Kalthom; Zainuddin, Mohamad Zahir (Scottish Journal of Arts, Social Sciences and Scientific Studies (SJASS)., 2012)

(untitled)
In the leadership communication styles, most of the middle management positions such as managers, assistant managers and those at executives’ level are practicing good leadership communication via enhancing the Islamic quality at Malaysian Public Service. A two-way communication does exist among the staff especially in meetings, discussions and working in team. A good leadership communication among the staff and their involvement are important in Malaysian Civil Service in order to achieve the total quality management objective. Reason being is that the leadership communication is the most important tool and vital part in all organisational operations. Leadership communication could be the basis for understanding, cooperation, teamwork and positive action, which without it such goals would be undermined at Malaysian Civil Service. Two-way communication gives more opportunities to the staff to be involved in discussions and meetings which create the spirit of togetherness in the organisation. The Total Quality Management (TQM) has positively affected job satisfaction, the employees' ability to work together, improve the staff work and builds leadership communication at Malaysian Public Service. Obviously, provide a significance relationship between leadership communication and quality management in Islamic perspectives on job satisfaction among the staff at Malaysian Public Service. Keywords: Total Quality Management,